Pengaruh Work From Home Terhadap Kinerja Pegawai Kementerian Keuangan - Kukuh Hanna Prapanca; S. Agus Santoso; Dwi Putranto Riau (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
The sudden shift from a traditional work system to a remote work system / Work From Home (WFH) due to the COVID-19 pandemic raises questions about how this condition affects employee productivity and performance achievement. This study aims to analyze the impact of Work From Home (WFH) implementation on employee performance at the Regional Office of the Directorate General of Taxes East Java III during the 2019–2020 period. This study focuses on comparing Employee Performance Achievement (EPA / CKP) before and during WFH to understand whether this policy has a significant impact on employee performance. Employee performance in this study is measured based on annual CKP, which includes assessments from direct supervisors and the achievement of Key Performance Indicators (KPI / IKU). The analysis was conducted using regression methods in the SMART PLS software, with independent variables including gender, age range, job cluster, and office location. The study results indicate a decline in the average CKP during WFH, although the degree of decline varies. Employees whose jobs require direct interaction with taxpayers (TP / WP) experienced a more significant impact than those who do not interact directly. From a demographic perspective, female employees demonstrated better performance resilience than male employees, while younger employees adapted more easily to remote work patterns than senior employees. Conversely, office location did not have a significant influence on changes in employee performance due to the relatively equal technological infrastructure across the research area. This study concludes that WFH implementation has varying impacts on employee performance at Regional Office of the Directorate General of Taxes East Java III. In general, there was a decline in the average CKP during WFH, indicating challenges in adjusting to remote work patterns. However, some employees managed to adapt to this work system and even showed improved performance. The study results also indicate that the examined variables have not fully captured the factors influencing employee performance comprehensively, suggesting the need for further research to explore other variables contributing to changes in employee performance during WFH.